Perceptions of Human Nature in Celtic Tradition: Significance of the Figure of the Bird - Gedžiūtė, Audronė (Tautosakos darbai, 2019)
The article deals with dualistic perception of human nature as reflected in Celtic mythopoetics of death. By relying on linguistic data, various ancient Celtic texts and episodes from the epic heroic literature, the article tackles questions concerning relations between the body as the material part of a person and the soul as the spiritual one. Various hypotheses concerning significance of the figure of the bird are verified: whether the bird stands for the soul of the dead, operates as a psychopomp or is involved in the process of metempsychosis. The analysis reveals operational mechanism of the bird in the context of love and death, significance of shapeshifting into a bird, and instrumental use of the bird in situations related to the death-like state.
Keywords: Celtic tradition; myth; death; dualism; bird